2021
DOI: 10.1002/anie.202100668
|View full text |Cite
|
Sign up to set email alerts
|

RuV‐Acylimido Intermediate in [RuIV(Por)Cl2]‐Catalyzed C–N Bond Formation: Spectroscopic Characterization, Reactivity, and Catalytic Reactions

Abstract: Metal-catalyzed CÀNb ond formation reactions via acylnitrene transfer have recently attracted muchattention, but direct detection of the proposed acylnitrenoid/acylimido M-(NCOR) (R = aryl or alkyl) species in these reactions poses af ormidable challenge.H erein, we report on Ru(NCOR) intermediates in CÀNb ond formation catalyzed by [Ru IV -(Por)Cl 2 ]/N 3 COR, ac atalytic method applicable to aziridine/ oxazoline formation from alkenes,a mination of substituted indoles, a-amino ketone formation from silyl eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…Since Breslow's initial reports on catalytic C−H amination using an iron porphyrin catalyst [1,2] there has been substantial interest in directly converting hydrocarbons into amines [3,4] . In subsequent reports, late transition metals such as Ru, [5–7] Rh, [8,9] Mn, [10] Co, [11–14] Ni, [15,16] and Cu [17–22] have been successfully utilized as catalysts for C−H amination reactions. Iron remains of particular interest due to its relevance in cytochrome P450 enzymes that catalyze the analogous hydroxylation of C−H bonds [23,24] .…”
Section: Methodsmentioning
confidence: 99%
“…Since Breslow's initial reports on catalytic C−H amination using an iron porphyrin catalyst [1,2] there has been substantial interest in directly converting hydrocarbons into amines [3,4] . In subsequent reports, late transition metals such as Ru, [5–7] Rh, [8,9] Mn, [10] Co, [11–14] Ni, [15,16] and Cu [17–22] have been successfully utilized as catalysts for C−H amination reactions. Iron remains of particular interest due to its relevance in cytochrome P450 enzymes that catalyze the analogous hydroxylation of C−H bonds [23,24] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Che et al reported [Ru IV (Por)Cl 2 ]catalyzed C−N bond formation reactions using olefine and acyl azides as the substrates. 8 Although there are a number of elegant reports on the regioselective olefination/alkylation/coupling reaction of alkenes with ketones, the activation sites of the above reactions are mainly located in the ortho C−H bond of the aryl ring or carbonyl substituent in ketones. 9 As a special functional olefin, para-quinone methides (p-QMs) has been regarded as a very important synthon.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is essential to add oxidants in the above reactions to promote the formation of free radical intermediates. In addition, Che et al reported [Ru IV (Por)­Cl 2 ]-catalyzed C–N bond formation reactions using olefine and acyl azides as the substrates …”
Section: Introductionmentioning
confidence: 99%
“…The M = X (X = C, carbene; X = N, nitrene) unit has been proposed as an important reactive intermediate in transitionmetal-catalyzed processes, and some of which have been successfully detected or isolated. [1,2] In recent years, catalytic conversions based on the active M = X intermediate have been emerged as a powerful tools to construct new CÀ C and CÀ X bonds. [3,4] Among these transformations, the transition-metalcatalyzed formal cycloaddition of C=C bonds through carbene or nitrene transfer are the most efficient paths to synthesize three-membered strained cyclopropane or aziridine derivatives.…”
Section: Introductionmentioning
confidence: 99%